Lung parenchymal changes in patients with ankylosing spondylitis - Hasiloglu, Zehra Isik (Baishideng Publishing Group Co., Limited, 2012)
AIM: To assess lung parenchymal changes in ankylosing spondylitis (AS) using high resolution computed tomography (HRCT). METHODS: We included 78 AS patients whose average age was 33.87 (18-56) years with a ratio of 53 males to 25 females who were followed up for 3.88 (1-22) years on average. Pneumonia and tuberculosis were excluded. In a detailed examination of lung HRCT findings, we investigated the presence of parenchymal micronodules, parenchymal bands, subpleural bands, interlobular and intralobular septal thickening, irregularity of interfaces, ground-glass opacity, consolidation, mosaic pattern, bronchial wall thickening, bronchial dilatation, tracheal dilatation, pleural thickening, emphysema, thoracic cage asymmetry, honeycomb appearance, structural distortion, apical fibrosis and other additional findings. RESULTS: In detailed HRCT evaluations, lung parenchymal changes were found in 46 (59%) of all patients. We found parenchymal bands in 21 (27%) cases, interlobular septal thickening in 9 (12%), emphysema in 9 (12%), apical fibrosis in 8 (10%), ground-glass opacities in 7 (9%), parenchymal micronodules in 5 (6%), irregularity in interfaces in 3 (4%), bronchial dilatation in 3 (4%), mosaic pattern in 2 (3%), pleural thickening in 2 (3%), consolidation in 1 (1%), bronchial wall thickening in 1 (1%) and a subpleural band in 1 (1%) case. Furthermore, we detected subsegmental atelectasis in 2 patients and a cavitary lesion in 1 patient. CONCLUSION: Our study had the highest number of AS cases of all previous studies in evaluating lung parenchymal changes. The rate of lung parenchymal changes was slightly lower than that reported in recent literature.